'Framing figures' and the campaign for sex purchase criminalisation in Ireland: A Lakoffian analysis. Issue 3 (December 2020) - Ward, Eilís
If the concept of social justice posits equality and fairness between subjects in the social order, then the presence of those subjects within that order must first and foremost be acknowledged. In Ireland's recent reform of prostitution law contained in the Criminal Law (Sexual Offences) Act 2017, the presence of the sex worker as a rights-bearing subject or citizen, with access to justice in that capacity, was denied. In this article I focus on the use of data by the neo-abolitionist 'Turn off the Red Light' campaign to 'flatten out' the complexity of sex workers lives and present the figure of the 'vulnerable prostituted woman' and the 'trafficking victim': tragic, abject, a necessarily violated person and in need of 'protection' from the state. I argue that this data, entering public and political discourse as uncontestable truth, constituted what I call, 'framing figures', framing an inevitable outcome and precluding certain subjects from the status of equality and fairness. The data allowed campaigners for the Sex Purchase Ban (SPB), and, in turn the state, to eclipse a social justice approach to sex work, such as proposed by the Sex Workers Alliance of Ireland and other actors.